Determining Crystal Field Distortions of YVO(3) though X-ray Scattering - Beale, T; Johnson, R; Bland, SR; Hatton, P; Bouchenoir, L; Boothroyd, A; Prabhakaran, D (Trans Tech Publications Ltd, 2009)
We present resonant x-ray scattering experimental data from YVO 3. By scattering at the vanadium K edge we are able to observe diffraction from the anisotropic tensor of susceptibility at the Bragg forbidden (010). The resonant energy spectra from these reflections are unusually complex, giving an indication of the crystal field distortions around the vanadium site.